Bacillus licheniformis-based intensive fermentation of Tibetan tea improved its bioactive compounds and reinforced the intestinal barrier in mice - Zhu, Hui; Zhou, Xiaoli; Shen, Caihong; Ao, Zonghua; Cao, Xiaonian; Song, Chuan; Mehmood, Muhammad Aamer; Wu, Tao; Mei, Jie; He, Manli; Ma, Yi; Wang, Ning (Frontiers in Microbiology, 2024)
Tibetan tea changes during microorganism fermentation. Research on microorganisms in Tibetan tea has focused on their identification, while studies on the influence of specific microorganisms on the components and health functions of Tibetan tea are lacking. This study isolated Bacillus licheniformis from Tibetan tea and studied its impact on tea; the resulting metabolites (polyphenols, alkaloids, terpenoids, amino acids, and lipids) were analyzed using liquid chromatography with tandem mass spectrometry (UHPLC-TOF-MS). Compared to non-fermented Tibetan tea, B. licheniformis-fermented tea exhibited increased levels of the bioactive compounds, whereas those of some catechins and lipids decreased. Histological assays and fluorescence quantitative polymerase chain reaction analyses using mice indicated that fermentation improved antioxidant function and reinforced the intestinal barrier. Fermentation increased the relative abundance of beneficial microorganisms, such as short-chain fatty acid-producing bacteria, which can strengthen the intestinal barrier. Therefore, intensive fermentation with B. licheniformis can improve the health benefits of Tibetan tea.